Skrining Fitokimia dan Uji Antibakteri Nanopartikel Perak Ekstrak Daun Pepaya (Carica papaya L) terhadap Bakteri Staphylococcus epidermidis dan Salmonella typhi - Ni Made Suarjo Putri; Dwi Sutiningsih; Mochamad Hadi (JURNAL BIOS LOGOS, 2023)
Infections caused by bacteria are still common in developing countries, among them Staphylococcus epidermidis and Salmonella typhi. In Indonesia, papaya leaves (Carica papaya L.) are widely used as traditional medicine because they contain compounds that are antibacterial. The combination of silver nanoparticles with papaya leaves has the potential to increase antibacterial effectiveness. The purpose of this study was to determine the effectiveness of papaya leaf extract silver nanoparticles in inhibiting Staphylococcus epidermidis and Salmonella typhi bacteria. This research method is a true experiment with a post-test only design with a control group. The results showed that papaya leaf metabolites consisted of flavonoids, steroids, and tannins, while the total levels contained in flavonoids 791.209%, and tannins 11.138%. The diameter of the inhibition zone concentrations of 100, 150, 200, and 250 ppm proved that papaya leaf extract combined with silver nanoparticles had good antibacterial active compounds but was more powerful in killing Staphylococcus epidermidis bacteria than Salmonella typhi bacteria.